The Relationship between Body Image and Self-Confidence among Health Sciences Students - Dheny Sulistyaningrum; Arif Widodo (Indonesian Journal of Global Health Research, 2026)
University students are individuals who are in a transitional phase from late adolescence to early adulthood, characterized by various physical, psychological, and social changes. Body image is one psychological aspect related to how individuals perceive and evaluate their bodies. Body image can play a role in the development of self-confidence, which is needed to engage in academic and social activities. Self-confidence is a positive attitude that reflects an individual’s belief in their abilities, objective self-assessment, and the ability to act rationally and responsibly. Adequate self-confidence plays an important role in supporting learning processes, environmental adaptation, and students’ psychological well-being. Therefore, understanding the relationship between body image and self-confidence among university students is important. This study aimed to determine the relationship between body image and self-confidence among students of the Faculty of Health Sciences at Universitas Muhammadiyah Surakarta. This study employed a quantitative correlational design with a sample of 96 students selected using purposive sampling. Data were collected using body image and self-confidence questionnaires that had been tested for validity and reliability. Data analysis was conducted using Spearman correlation analysis. The results showed that most respondents had a moderate level of body image (74%) and a moderate level of self-confidence (54.2%). Spearman correlation analysis showed a p-value of 0.001 (p < 0.05) with a correlation coefficient of r = 0.557, indicating a positive relationship with moderate strength between body image and self-confidence. It can be concluded that there is a significant and positive relationship between body image and self-confidence among students of the Faculty of Health Sciences at Universitas Muhammadiyah Surakarta. The more positive an individual’s perception of their body, the higher their level of self-confidence.